Ask Questions, Get Answers

Want to ask us a question? Click here
Browse Questions
0 votes

The coefficient of $x^n$ in the expansion $(1+x)(1-x)^n$ is

$\begin{array}{1 1} =(-1)^n [1-n] \\ =(-1)^n [1+n] \\ =(-1)^{n-1} n \\ =(-1)^n [n-1] \end{array}$

Can you answer this question?

1 Answer

0 votes
Coefficient of $x^n$ in $(1+x)(1-x)^n$$= 1\times$ coeff. of $ x^n $ in $(1-x)^n+1\times$ coeff. of $x^{n-1}$ in $(1-x)^n$
$\therefore$ Coefficient of $x^n$ in $ (1+x)(1-x)^n$$=(-1)^n $$ ^nC_n $$+(-1)^{n-1}$$ ^nC_{n-1}$
$=(-1)^n [1-n]$
answered Sep 15, 2013 by rvidyagovindarajan_1

Related questions

Ask Question
student study plans
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App